Theory and Practice of Using Robotics in Educational Process - E. E. Ruslyakova; O. V. Pustovoitova; Yu. P. Kiseleva; L. A. Yakovleva (Высшее образование в России)
This article discusses the problem of using robotics in higher education, highlights the theoretical and practical aspects of the problem. The article describes the current trend of the inclusion of robotics in the educational process as one of the effective tools for the formation of students’ professional competencies, psychological readiness to implement educational programs at any level in the modern post-industrial world. The authors present psychological and pedagogical research, in which the organization of project work with fourth-grade and fifth-grade students was studied using a robot-assistant. Practical research was devoted to the perception of anthropomorphic robots by students. They studied a number of disciplines in direct contact with a static robot. The authors analyzed the possibility of using robotics in educational process while preparation of students majoring both in engineering and pedagogy. The results of this research support the idea that robots can be assistants for a teacher and motivators for students. Interaction between robot and students enhances their general emotional background, activates cognitive processes and learning in general.